Revealing conformational substates of lipidated N-Ras protein by pressure modulation - Kapoor, Shobhna (National Academy of Sciences, 2012)
Regulation of protein function is often linked to a conformational switch triggered by chemical or physical signals. To evaluate such conformational changes and to elucidate the underlying molecular mechanisms of subsequent protein function, experimental identification of conformational substates and characterization of conformational equilibria are mandatory. We apply pressure modulation in combination with FTIR spectroscopy to reveal equilibria between spectroscopically resolved substates of the lipidated signaling protein N-Ras. Pressure has the advantage that its thermodynamic conjugate is volume, a parameter that is directly related to structure. The conformational dynamics of N-Ras in its different nucleotide binding states in the absence and presence of a model biomembrane was probed by pressure perturbation. We show that not only nucleotide binding but also the presence of the membrane has a drastic effect on the conformational dynamics and selection of conformational substates of the protein, and a new substate appearing upon membrane binding could be uncovered. Population of this new substate is accompanied by structural reorientations of the G domain, as also indicated by complementary ATR-FTIR and IRRAS measurements. These findings thus illustrate that the membrane controls signaling conformations by acting as an effective interaction partner, which has consequences for the G-domain orientation of membrane-associated N-Ras, which in turn is known to be critical for its effector and modulator interactions. Finally, these results provide insights into the influence of pressure on Ras-controlled signaling events in organisms living under extreme environmental conditions as they are encountered in the deep sea where pressures reach the kbar range.